Effect of Prolonged Fasting Duration on 50 Gram Oral Glucose Challenge Test in the Diagnosis of Gestational Diabetes Mellitus - Hancerliogullari, Necati; Celik, Hatice Kansu; Karakaya, Burcu Kisa; Tokmak, Aytekin; Tasci, Yasemin; Erkaya, Salim; Engin-Ustun, Yaprak; Ozgu-Erdinc, A. Seval (Hormone and Metabolic Research, 2018)
The aim of this study was to investigate the association between fasting duration before screening with 50 g glucose challenge test (GCT) and the test outcome. For this cross-sectional study, we enrolled 508 low-risk pregnant women who underwent 50 g GCT between the 24 and 28 weeks of gestation. We excluded women with pregestational diabetes, multiple gestations or a history of gestational diabetes mellitus (GDM), and macrosomia. We evaluated fasting durations, GCT results, and demographic features. A significant positive correlation was found between fasting duration and 50 g GCT values (r=0.122; p=0.006), and the best cut-off value was found to be 6.5 h, with 85.85% sensitivity and 38.61% specificity (relative risk, 2.73; 95% CI, 1.893–3.936; p<0.0001). Further, we divided the patients into two groups: study (fasting, <6.5 h; n=146) and control (fasting,>6.5 h; n=362) groups. Notably, the mean glucose levels, number of patients with GCT>140 mg/dl, and rates of unnecessary 100 g loadings were significantly higher in the study group. We found no significant differences between the groups in terms of the fasting plasma glucose levels and GDM prevalence. According to our findings, fasting duration of>6.5 h resulted in 2.7 times more unnecessary 100 g glucose tolerance tests (GTT). We recommend that patients having fasted for>6.5 h receive a one-step 75 g GTT after completing 8-h fasting.
Keywords: glucose challenge test (GCT); oral glucose challenge test (OGCT); fasting duration; gestational diabetes mellitus